IMPLEMENTASI GOOGLE CLASSROOM SEBAGAI SARANA PEMBELAJARAN DARING PADA MASA PANDEMI COVID-19 DI KABUPATEN TUBAN - Alfian Nurlifa; Andy Haryoko; Ulfa Yuliasari (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2020)
The problem that often occurs in the world of education is the problem of knowledge transfer carried out by educators and students. The process of transferring knowledge has been carried out conventionally, namely by providing material face to face in a room or class. However, during the Covid-19 pandemic at this time this method could not be done. The current pandemic period requires people to maintain distance or social distancing. This social distancing encourages the emergence of online learning methods which are expected to reduce for the spread of virus in schools and college environment. Although online learning methods have been around for a long time, not all students are accustomed to using these methods. One of the online learning methods that can be done is by using google classroom. The use of google classroom is expected to increase the independence of students to learn and truthfully express ideas and questions other benefits of online learning.